SEKOLAH DAN PENDIDIKAN KARAKTER ISLAMI (Sebuah Analisis Konseptual) - Ramin, Ramin (TARBAWY : Indonesian Journal of Islamic Education, 2020)
Abstract. The problem of the nation’s character until now and even in the future remains an interesting discussion for practitioners and observers. Thinking about the right formula to educate the character of the young generation as the nation’s successors is baing more focused in this country now. The busyness of parents, social environment, community, and social media have a role in shaping adolescent behavior. Adolescents are frequently affected to take actions that reflect bad character. This article is the result of deep thinking with the literature review method on the importance of schools taking a role in educating adolescent characters from references that specifically discuss the theories of character education models. School is a formal institution that possibly changes the role of the family in transferring good character values to students through the form of intra-curricular, co-curricular, extra-curricular, and habituation activities. The end of this article recommends that stakeholders should conceptually know well about the design, model, and character education approach that will be applied. Abstrak. Masalah karakter bangsa hingga saat ini dan bahkan ke depan masih tetap menjadi diskusi yang menarik bagi praktisi dan pemerhati. Memikirkan formula yang tepat untuk mendidik karakter generasi muda sebagai penerus bangsa adalah fokus yang lebih mengemuka di tanah air ini. Kesibukan orang tua, lingkungan sosial, komunitas, dan termasuk media sosial memiliki andil dalam membentuk perilaku remaja. Tak jarang para remaja terpengaruh, hingga melakukan tindakan-tindakan yang mencerminkan karakter yang buruk. Artikel ini merupakan hasil pemikiran mendalam dengan metode literatur review mengenai pentingnya sekolah mengambil peran dalam mendidik karakter remaja dari referensi yang khusus membahas tentang teori-teori model pendidikan karakter. Sekolah adalah organisasi formal yang sangat memungkinkan mengganti peran keluarga dalam mentransfer nilai-nilai karakter yang baik kepada siswa melalui bentuk kegiatan intra kurikuler, ko-kurikuler, ekstra kurikuler, maupun pembiasaan. Akhir dari artikel ini merekomendasikan bahwa stakehorders harus matang secara konseptual mengenai desain, model, dan pendekatan pendidikan karakter yang akan diaplikasikan.